2007
DOI: 10.3168/jds.2007-0080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Concentrated Lidocaine Solution on the Acute Phase Stress Response to Dehorning in Dairy Calves

Abstract: The objective of this study was to more fully define the surgical stress response to dehorning by heat cauterization in dairy calves by measuring behavioral, hormonal, inflammatory, and immunological markers of stress and to determine whether a nerve block of the surgical site with a concentrated solution of lidocaine (5%) reduces the degree of stress. Thirty-two 10- to 12-wk-old female Holstein calves were randomly allotted to 1 of 4 treatments: 5% lidocaine followed by dehorning, 2% lidocaine followed by deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 25 publications
(41 reference statements)
6
47
4
2
Order By: Relevance
“…This may be due to species variation or different environmental conditions. Present findings, for cortisol, were in agreement with the observations of workers like Doherty et al (2007), Alvarez et al (2009) and Alvarez and Gutiérrez (2010). Higher concentration of the serum cortisol in D L + M , before and after disbudding, may be due to fear of thrice handling to animals of this group, i.e., once for hair cutting and twice for medication.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This may be due to species variation or different environmental conditions. Present findings, for cortisol, were in agreement with the observations of workers like Doherty et al (2007), Alvarez et al (2009) and Alvarez and Gutiérrez (2010). Higher concentration of the serum cortisol in D L + M , before and after disbudding, may be due to fear of thrice handling to animals of this group, i.e., once for hair cutting and twice for medication.…”
Section: Discussionsupporting
confidence: 82%
“…observed increased lymphocyte and monocyte with a mild eosinopenia under conditions like excitement and stress in ruminants. These findings were in agreement with Doherty et al (2007) who observed that the percentage of circulating neutrophils was greatest (P < 0.001) at 12 hours with saline-and 2% lignocaine -treated animals; however higher neutrophil:lymphocyte ratio in lignocaine-treated group may be due to species difference. Findings of serum biochemistry can be correlated with rise or fall in different hormones especially cortisol.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Ballou et al [20] reported that giving local anaesthetic and a systemic analgesic prevented the decrease in supernatant concentrations of TNF-α among surgical castration or dehorning procedure in calves. Leukocytosis and neutrophilia were previously reported following hot-iron dehorning in calves [21] . In our study, it was determined that TNF-α concentrations increased at 15 min after disbudding in both groups however, this increment was higher in control group than those in DEX group (P<0.05).…”
Section: Tablo 2 Dexketoprofen Trometamol Ve Kontrol Gruplarında Boymentioning
confidence: 99%